Morphology and biology of Polydora hoplura Claparède, 1868 (Annelida: Spionidae) - Radashevsky, Vasily I.; Choi, Jin-Woo; Gambi, Maria Cristina (Zootaxa, 2017)
Polydora hoplura Claparède, 1868 is one of the largest species among congeners, attaining 6 cm in length and 2 mm in width for more than 200 chaetigers. It is a harmful shell-borer unintentionally transported with objects of aquaculture across the world. Brief original description and absence of type material resulted in confusion with the identification of this species. Herein, we review previous records, establish a neotype and redescribe P. hoplura based on newly collected material from the type locality, the Gulf of Naples. We also describe worms from other localities in Italy, illustrate adult morphology and report gradual development of taxonomic features of this species in ontogenesis based on material from South Korea.